2014 IEEE International Conference on Software Maintenance and Evolution 2014
DOI: 10.1109/icsme.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Source Code Disruption Caused by Automated Remodularisation Tools

Abstract: Abstract-Current software remodularisation tools only operate on abstractions of a software system. In this paper, we investigate the actual impact of automated remodularisation on source code using a tool that automatically applies remodularisations as refactorings. This shows us that a typical remodularisation (as computed by the Bunch tool) will require changes to thousands of lines of code, spread throughout the system (typically no code files remain untouched). In a typical multi-developer project this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Therefore, apart from decreasing the cohesion of the system, a Bunch re-modularisation might also be unrealistic because developers rarely create new packages to accommodate existing classes. This observation adds evidence to recent claims [13][11] against "Big Banlowere-modularisation approaches (i.e., a complete re-allocation of the system's classes in packages), where recent studies have used the original modular structure implemented by developers as a guide to find more suitable packages for certain classes [1] [8].…”
Section: Rq2: What Is the Relationship Between Raw Cohesion And The Mmentioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, apart from decreasing the cohesion of the system, a Bunch re-modularisation might also be unrealistic because developers rarely create new packages to accommodate existing classes. This observation adds evidence to recent claims [13][11] against "Big Banlowere-modularisation approaches (i.e., a complete re-allocation of the system's classes in packages), where recent studies have used the original modular structure implemented by developers as a guide to find more suitable packages for certain classes [1] [8].…”
Section: Rq2: What Is the Relationship Between Raw Cohesion And The Mmentioning
confidence: 56%
“…A previous study by Hall et al [13] measured how many lines of code ought to be added/changed in order to apply solutions found by search based modularisation approaches. Apart from showing that developers would have to change up to 10% of their code base to adopt solution proposed by automated approaches, they also showed that the LOC to be changed strongly correlates with the modular structure disruption metric MoJoFM [56].…”
Section: Modular Structure Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Misplaced Class represents a class located in a package that contains other classes that are not related to its function [36], [82], [97]. The interest in these code smells is dictated by the fact that they have been recognized as important threats to the maintainability of a software system [1], [40], [48], [50], [97], [109], but also because they are considered harmful by developers [73].…”
Section: Textual and Structural Code Smell Detectionmentioning
confidence: 99%
“…At the same time, our results might be affected by the presence of the socalled "conceptual" false positives [31], i.e., code smell instances identified by detection tools as true positives but not perceived as such by developers. However, we limited this threat by investigating code smell types that previous research found to be critical for developers [40], [73], thus focusing on code smell instances likely to be perceived by developers as actual design problems.…”
Section: Threats To Validitymentioning
confidence: 99%